Regulating Private Higher Education in South Africa - Sehoole, Chika (International Higher Education, 2012)
This article makes case of how South Africa has been able to use its laws and policies to achieve its objectives of regulating private higher education. This happened in the context of an ascendancy of neo-liberal policies which favoured deregulation and the rolling back of the state. Through these policies the government was able to protect the public even during the global financial crisis as it had registered credible and financially sound institutions which could weather off the financial crises which affected many private companies worldwide.